The effect of product quality, price, and promotion on the purchase decision of Honda Beat motorcycles - Alfina Anggraeini; Shiwi Angelica Cindiyasari (Universitas Nusa Cendana, 2026)
The fierce rivalry within the automatic motorcycle industry underscores the urgency of decoding consumer behavior to sustain market dominance. This quantitative survey-based research evaluates the contribution of product quality, pricing strategies, and promotional activities toward the purchasing decisions of Honda Beat consumers in Bandar Lampung. Primary data gathered from 170 active users were synthesized utilizing multiple linear regression analysis via IBM SPSS Statistics. The empirical outcomes demonstrate that, partially, product quality, price, and promotion exert a positive and significant influence on purchase selection. Manufacturing quality emerges as the primary determinant, mirroring consumers' strict emphasis on vehicle reliability and operational durability. Furthermore, competitive pricing and aggressive promotional outreach effectively expand brand awareness and market preference. Simultaneously, the convergence of these three explanatory variables significantly shapes consumer purchasing decisions, thereby underlining the strategic necessity for manufacturers to cohesively execute these marketing pillars to secure a sustainable competitive advantage. Keywords: Product Quality; Price; Promotion; Purchase Decision